The fibroblast growth factor system in cognitive disorders and dementia - Zhai, Wujianwen; Zhang, Tong; Jin, Yujing; Huang, Shijing; Xu, Manman; Pan, Juhua (Frontiers in Neuroscience, 2023)
Cognitive impairment is the core precursor to dementia and other cognitive disorders. Current hypotheses suggest that they share a common pathological basis, such as inflammation, restricted neurogenesis, neuroendocrine disorders, and the destruction of neurovascular units. Fibroblast growth factors (FGFs) are cell growth factors that play essential roles in various pathophysiological processes via paracrine or autocrine pathways. This system consists of FGFs and their receptors (FGFRs), which may hold tremendous potential to become a new biological marker in the diagnosis of dementia and other cognitive disorders, and serve as a potential target for drug development against dementia and cognitive function impairment. Here, we review the available evidence detailing the relevant pathways mediated by multiple FGFs and FGFRs, and recent studies examining their role in the pathogenesis and treatment of cognitive disorders and dementia.